Unbalanced low coherence interference microscopy. (April 2022) - Ahmad, Azeem; Habib, Anowarul; Dubey, Vishesh; Ahluwalia, Balpreet Singh
Highlights: Low coherence interference microscopy (LCIM) is implemented with non-identical objective lenses in the object and the reference arm for the first time to the best of our knowledge. This is also called unbalanced optical configuration. This opens the flexibility to achieve scalable field of view and resolution in LCIM system, which is not done previously. This is demonstrated by imaging HeLa cells using three different 10 × /0.25, 20 × /0.45 and 60 × /1.2 NA objective lenses in the object arm with fixed reference arm objective lens using LCIM system. As different objective lenses have different amount of optical dispersion, therefore, its effect on the spatial phase sensitivity of LCIM is systematically studied by utilizing unfiltered white light and filtered white light (generated by inserting different bandpass filters of spectral bandwidths 69 nm, 10 nm, and 3 nm) in LCIM. Phase shifting based phase recovery using advanced iterative algorithm (AIA) is integrated with principal component analysis (PCA) algorithms for quadratic phase error compensation to recover accurate phase images of the test specimens. The accuracy of their integration is tested with standard double exposure method. The present approach is not limited to the integration of AIA and PCA algorithms for quadratic phase aberration free phase recovery. Any combination of phase shifting and aberration removal algorithms can be utilized for the scalable field of view phase imaging. Abstract: Low coherence interference microscopy (LCIM) provides high spatial phase sensitivity, i.e., speckle free and coherent noise free quantitative phase images of the test specimens. Due to low temporal coherence (TC) length of the light source, LCIM requires precise adjustment of the optical path difference (OPD) between the object and the reference arm, which is only a few micrometers. Consequently, previously demonstrated LCIM systems are implemented with the use of identical objective lenses in both the arms and also known as balanced interferometric configuration. The use of identical objective lens hinders both the use of high numerical aperture objective lens and also the swift change of the objective lens during imaging. In the present work, LCIM is implemented with non-identical objective lenses in the object and the reference arm also called unbalanced optical configuration. A range of objective lenses 10 × /0.25NA, 20 × /0.45NA and 60 × /1.2NA are employed in the object arm of the system while keeping single objective lens 10 × /0.25NA in the reference arm. To resolve the challenges associated with unbalanced configuration, advanced iterative algorithm (AIA) and principal component analysis (PCA) algorithms are integrated to recover quadratic phase error free phase images of the test specimens. The capabilities of the proposed method are exhibited on various specimens like USAF resolution, step-like test object and for the biological cells, HeLa cells. The proposed approach enables scalable magnification and resolution by simply rotating the imaging objective turret without the need of changing objective lens in the reference arm.